2021
DOI: 10.1111/jac.12542
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature stress during the flowering period alters the source–sink relationship and grain quality in field‐grown late‐season rice

Abstract: Late‐season rice, a major contributor to the production of high‐quality rice in China, often experiences low temperatures during the flowering period. The objective of this study was to determine the effect of low temperature stress on grain quality and to identify related physiological factors in late‐season rice. Sink and source characteristics and grain quality traits of two high‐quality late‐season rice cultivars were compared between a year in which low temperatures occurred during the flowering period (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…Our previous results with this same experiment showed that LTS after flowering did not significantly decrease grain weight, except under D3T4 treatment in Nanjing 46 ( Ali et al, 2021 ). And this result was similar to the previous studies ( Huang et al, 2021 ; Shi et al, 2021 ). Therefore, we assume that the main reason for the dilution effect of the amino acids content could be the decreasing grain number due to reduced seed-setting rate under LTS, as reported in our previous study ( Ali et al, 2021 ), and the decreasing grain number under LTS could significantly reduce the sink capacity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our previous results with this same experiment showed that LTS after flowering did not significantly decrease grain weight, except under D3T4 treatment in Nanjing 46 ( Ali et al, 2021 ). And this result was similar to the previous studies ( Huang et al, 2021 ; Shi et al, 2021 ). Therefore, we assume that the main reason for the dilution effect of the amino acids content could be the decreasing grain number due to reduced seed-setting rate under LTS, as reported in our previous study ( Ali et al, 2021 ), and the decreasing grain number under LTS could significantly reduce the sink capacity.…”
Section: Discussionsupporting
confidence: 93%
“…LTS has been shown to affect the content of several nutrient in rice grains ( Jia et al, 2015b ; Huang et al, 2021 ). There were several possible reasons for LTS effects on content of amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…About 100 mg samples of the cooked rice were subjected to in vitro digestion to determine the amount of glucose produced per unit fresh weight at six digestion times (15, 60, 120, 180, 240, and 300 min) using a Glycemic Index Analyzer (NutriScan GI20; Next Instruments, Condell Park, NSW, Australia). The starch digestion process of the cooked rice (i.e., the change in the amount of glucose produced over time) was fitted to the exponential association model for calculating starch digestion parameters, including active digestion duration, total glucose production, and glucose production rate ( Huang et al, 2021 ).…”
Section: Sampling and Measurementsmentioning
confidence: 99%
“…Low temperature (LT) is an important abiotic stress that seriously affects the production and development of global cereal crops (Huang et al, 2021;Zhang et al, 2021). Several studies have found that the post-silking/grain filling stage is very sensitive to LT during the growth cycle of cereal crops (Thakur et al, 2010;Luo, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Starch and protein are important components in grains, and the dynamics of their content and accumulation determines the yield of cereal crops (Lu et al, 2014a;Huang et al, 2021;Zhang et al, 2021). In cereal grains, starch and protein biosynthesis is a complex process determined by the coordinated action of enzymes (Marschner, 2011;Ran et al, 2020).…”
Section: Introductionmentioning
confidence: 99%